Mengeksplorasi Tantangan dan Manfaat Implementasi Sistem Informasi Manajemen Kepegawaian - Arya Tunggal Narotama; Ines Heidiani Ikasari (Shofanah Media Berkah, 2023)
The implementation of the Human Resource Management Information System (HRMIS) faces complex challenges in managing human resources across various organizations. This study aims to explore the challenges and opportunities of HRMIS implementation in a modern organizational context. Through a systematic literature review, key factors influencing HRMIS implementation, including technical, managerial, organizational, and social aspects, were identified. Challenges that may arise in adopting HRMIS, such as user resistance, resource limitations, and the complexity of user requirements, were analyzed. The results of the literature analysis indicate that HRMIS implementation offers opportunities for organizations to improve efficiency, accuracy, and transparency in personnel management. However, the challenges faced in implementation must be considered. Factors such as organizational cultural change, integration with existing systems, adequate user training, and strong management support are crucial for the successful implementation of HRMIS. These findings provide valuable insights for practitioners and decision-makers in planning and executing HRMIS implementation. By understanding the potential challenges and optimizing available opportunities, organizations can enhance the effectiveness and efficiency of personnel management. This study also serves as a basis for further research, including comparative analysis of HRMIS implementation in the public and private sectors, as well as evaluating the long-term impact of HRMIS usage on organizational performance.